An experimental analysis of egg-retrieval response of the Eurasian Stone curlew (Burhinus oedicnemus). Issue 1 (2nd January 2020) - Spena, Maria T.; Grasso, Rosario; Cannavò, Vanessa; Baldaccini, Natale E.
Abstract : Egg retrieval is a common behaviour among ground-nesting birds and a key part of their parental care. This paper deals with an experimental study of that behaviour in four Sicilian populations of Stone curlew, considering not only the success in retrieving but also the time latency in the bird reacting to the sight of an egg displaced from its nest and the relative retrieval time, which are two parameters that have been ignored until now by other studies. Egg displacements were made in 36 nests at the same distance of 50 cm. In each nest, two egg displacements were made, one in the first and the other in the second half of the brooding period, at a mean distance of 12.5 ± 3.5 days. In only seven out of 67 valid tests, the egg remained unretrieved, confirming the ability of Stone curlew to roll in their eggs. None of the factors considered as predictors had a significant effect on the success of the retrieval. Latency and retrieval times resulted positively correlated to each other, and were not statistically different among the four populations tested, nevertheless, showing a high variability even within the same population. In nine cases the retrieval was performed by the two parents acting in turn, however, in these cases the retrieval and not the latency times turned out to be longer with respect to the retrievals made by only one bird. When the retrieval times of the first displacement were compared to those of the second, the latter were shorter. The retrieval times are influenced by the ground conformation, being shorter in agricultural sites where the ground is plain and levelled. Indeed the GLMM analyses suggest a significant influence of different external factors on both the latency and retrieval times.